Three phylogenetic groups have driven the recent population expansion of Cryptococcus neoformans - P. M. Ashton (Nature Portfolio, 2019)
Cryptococcus neoformans is an opportunistic fungal pathogen which primarily affects people with immune defects including those living with HIV. Here, the authors sequence and analyze genomes of 699 isolates, and identify recent population expansion driven by three phylogenetic groups.